2023
DOI: 10.3390/genes14112039
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Clinical Phenotype in TARDBP Mutations: Amyotrophic Lateral Sclerosis Case Description and Literature Review

Michele Lombardi,
Lucia Corrado,
Beatrice Piola
et al.

Abstract: Mutations in the 43 kDa transactive-response (TAR)-DNA-binding protein (TARDBP) are associated with 2–5% of familial Amyotrophic Lateral Sclerosis (ALS) cases. TAR DNA-Binding Protein 43 (TDP-43) is an RNA/DNA-binding protein involved in several cellular mechanisms (e.g., transcription, pre-mRNA processing, and splicing). Many ALS-linked TARDBP mutations have been described in the literature, but few phenotypic data on monogenic TARDBP-mutated ALS are available. In this paper, (1) we describe the clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Variants in this gene are common in sALS cases [ 29 ]. Although previous studies have identified variants mostly in exon 6 [ 61 ], we found variants that span the whole coding sequence. Only one of the variants we found has been recorded before in ALS cases (c.995G>T p.G297V) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Variants in this gene are common in sALS cases [ 29 ]. Although previous studies have identified variants mostly in exon 6 [ 61 ], we found variants that span the whole coding sequence. Only one of the variants we found has been recorded before in ALS cases (c.995G>T p.G297V) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 57%
“…In that specific region, we found 11 genetic variants, 2 missense and probably damaging (c.781A>G p.R226G; c.1326G>T p.K407N), 5 possibly damaging [c.1001G>A (p.G299E); c.1001G>A (p.G299E); c.1180C>A (p.Q326R); c.1322C>T (p.S406F); c.1328C>T (p.S408F)] and the c.995G>T variant, which has previously been associated with ALS. This region is encoded primarily by triplets located in exon 6, where most genetic variants have been recorded [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of sequencing techniques and increasingly accessible screening in the clinic has identified rare TARDBP mutations also in clinical neurodegenerative pathologies other than ALS and FTD, such as semantic primary progressive aphasia (svPPA) ( Caroppo et al, 2016 ; Gelpi et al, 2014 ), flair arms ( Moreno et al, 2015 ), classical Parkinson's disease and atypical Parkinsonism (progressive supranuclear palsy and corticobasal syndrome) ( Chen et al, 2021 ; Tiloca et al, 2022 ) and autosomal dominant myopathy ( Zibold et al, 2023 ). Moreover, despite the low prevalence of TARDBP mutations, there are a few reported cases of ALS patients carrying homozygous mutations (p.A382T and p.G294V) that do not seem to lead to overtly severe phenotypes ( Borghero et al, 2011 ; Cannas et al, 2013 ; Corrado et al, 2020 ; Lombardi et al, 2023 ). Indeed, patients carrying different TARDBP mutations have heterogeneous clinical phenotypes that, at least in the case of ALS, seem to be more often associated with upper motor neuron dysfunction ( Lombardi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite the low prevalence of TARDBP mutations, there are a few reported cases of ALS patients carrying homozygous mutations (p.A382T and p.G294V) that do not seem to lead to overtly severe phenotypes ( Borghero et al, 2011 ; Cannas et al, 2013 ; Corrado et al, 2020 ; Lombardi et al, 2023 ). Indeed, patients carrying different TARDBP mutations have heterogeneous clinical phenotypes that, at least in the case of ALS, seem to be more often associated with upper motor neuron dysfunction ( Lombardi et al, 2023 ). This heterogeneity is also a feature of phenotypes arising in the different published TDP-43 KI mouse models ( De Giorgio et al, 2019 ), with only the M323K and N390D ( Huang et al, 2020 ) reported mutations leading to a degree of lower motor neuron degeneration, with distal NMJ dysfunction also reported in M337V and G298S mutants ( Ebstein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite the low prevalence of TARDBP mutations, there are a few reported cases of ALS patients carrying homozygous mutations (p.A382T and p.G294V) that do not seem to lead to overtly severe phenotypes (Borghero et al, 2011; Cannas et al, 2013; Corrado et al, 2020; Lombardi et al, 2023). Indeed, patients carrying different TARDBP mutations have heterogeneous clinical phenotypes that, at least in the case of ALS, seem to be more often associated with upper motor neuron dysfunction (Lombardi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%